2020
DOI: 10.1002/ehf2.12795
|View full text |Cite
|
Sign up to set email alerts
|

Biventricular imaging markers to predict outcomes in non‐compaction cardiomyopathy: a machine learning study

Abstract: Aims Left ventricular non-compaction cardiomyopathy (LVNC) is a genetic heart disease, with heart failure, arrhythmias, and embolic events as main clinical manifestations. The goal of this study was to analyse a large set of echocardiographic (echo) and cardiac magnetic resonance imaging (CMRI) parameters using machine learning (ML) techniques to find imaging predictors of clinical outcomes in a long-term follow-up of LVNC patients. Methods and results Patients with echo and/or CMRI criteria of LVNC, followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Machine learning procedures have been successfully used to guide diagnosis, 78 therapeutic strategies, 79 and prognosis 80 . Using a machine learning algorithm, Adler et al .…”
Section: Diagnosis and Prognosismentioning
confidence: 99%
“…Machine learning procedures have been successfully used to guide diagnosis, 78 therapeutic strategies, 79 and prognosis 80 . Using a machine learning algorithm, Adler et al .…”
Section: Diagnosis and Prognosismentioning
confidence: 99%
“…[17][18][19] Therefore, investigating the prognosis of patients with LVNC has significant clinical implications. Many studies have been conducted to predict the risk of MACE in patients with LVNC using the thickness of non-compacted myocardium and LV trabeculated mass, atrial size, LVEF, LGE, brain natriuretic peptide, and genes 3,7,[19][20][21][22][23] with LVEF and LGE being the most commonly used predictors. 3,24 Howev-er, Yu et al 25 found that even patients with LVEF-preserved LVNC could have impaired LV systolic function and were at risk for MACE.…”
Section: Discussionmentioning
confidence: 99%
“…ML techniques have been implemented for improving risk stratification in these patients. Specifically, echocardiographic and CMR data were analyzed using ML algorithms to identify predictors of adverse events in non-compaction cardiomyopathy patients [ 37 ]. The combination of CMR-derived left ventricular ejection fraction, CMR-derived right ventricular end systolic volume, echocardiogram-derived right ventricular systolic dysfunction and CMR-derived right ventricular lower diameter was found to achieve the better performance in predicting major adverse events in these patients [ 37 ].…”
Section: Specific Patient Populationsmentioning
confidence: 99%